Experimental Research on the Effect of Thermophysical Characteristics of Cutting Fluid on Cutting Performance During Turning Ti-6Al-4V Alloy - Xiaorong Zhou; Lin He; Sen Yuan; Jing Deng; Zebin Su; Jingdou Yang; Feilong Du (Lubricants)
Cutting fluid has been widely used to enhance the heat dissipation of cutting systems. However, whether cutting fluid can fully play its role is closely correlated with its thermophysical characteristics, such as viscosity, surface tension, etc. In this work, to study the effect of the thermophysical characteristics of cutting fluid on cutting performance, three green vegetable oils (semi-synthetic fluid (L1), rapeseed oil (L2), canola oil (L3)) were selected as cutting fluids of the MQL system, and differences in cutting performance were compared and analyzed under varied lubrication environments. Firstly, the thermophysical characteristics of the vegetable oils were determined by experimental methods. Afterwards, parameters, including tool wear, cutting force, and temperature, as well as the quality of machined workpieces, were selected to evaluate cutting performance, and essential reasons for the difference in cutting performance under varied lubrication environments were clarified. The results demonstrated that the cutting force, cutting temperature, and tool wear produced in the three MQL environments were lower than those in the dry cutting environment, while only the L1 and L2 MQL environments exhibited higher machined surface quality than the dry cutting environment. Moreover, obvious differences in cutting performance under the three MQL environments were also observed due to the different thermophysical characteristics of the three vegetable oils. The best cutting performance was achieved when L2 was used as the MQL cutting fluid. The efforts of this study will give an important reference for the choosing of green cutting fluid in the cutting process of difficult-to-cut materials and be of great significance for accelerating the development of green processing.